Decision criteria for problem solving. An Industrial Engineer's Managerial Model - Acevedo Borrego, Adolfo (2012)
The aim of this study is to identify the criteria that the industrial engineer or manager as decision maker, applied to solve problems, for which you design the conceptual model approach to soft systems methodology and experimental design to validate the influence of criterion in the choice of the manager or decisor maker. Within the rational framework used in the management of organizations, the industrial engineer try to identify the criteria, as decision maker, applied to choose among options, and resolve problem situations of the various scenarios in which it operates and holds roles. The enterprise considers four types of decisional macrocriteria, related to the stage and the decision maker's perspective, they may include: a) Position, based on human nature, b) Optimization based on the achievement and action in the world real, c) Satisfaction, based on social regulation and behavior. d) Opportunity, based on predictions and contingencies. The study shows main criteria to make decisions and industrial engineer's preference for either, depending on the stage and the role that manage at time of election.